Agricultural Soil Carbon Sequestration: A Sustainable Solution to Climate Change - Lepcha, Tenzimit; Gobinath, R.; Suruchi, K.; Manisha; Tarun, N. (Chronicle of Bioresource Management, 2025)
As far as we know, numerous effects of climate change are felt throughout the entire earth system, including the ecosystem supporting agriculture. Increased concentrations of carbon dioxide (CO2) and other greenhouse gases are the primary cause of the earth’s rising temperature, attributed to changes in land use, and the burning of fossil fuels. Hereby carbon sequestration has emerged as a solution with implications of different practices with increasing the carbon pools as a goal. This article aims to understand the impact of agricultural practices on climate change and soil carbon sequestration as a solution to address the changes. It also underscores the challenges faced and shortcomings of soil carbon sequestration.